A Case Report of a Combined Bypass Surgery on Coronary Artery and Right Common Femoral Artery of the Aorta - (:unkn) unknown (My University, 2014)
Periferik vasküler operasyonlar, miyokard infarktüsü açısından yüksek risk taşımaktadır. Ciddi koroner arter hastalığı ve periferik vasküler sorunların aynı anda olduğu durumlarda mortalite ve morbiditeyi artırmayacak kombine girişimlerin hasta iyileşmesine olumlu etkileri olabilir. Altmış yedi yaşında erkek hasta, sağ alt extremitede istirahat ağrısı şikayeti ile polikliniğimize başvurdu. Yapılan tetkiklerinde sağ ana iliyak arterin tam tıkalı olduğu, sol ön inen ve arka inen koroner arterlerinde ciddi darlık bulunduğu saptandı. Kardiyopulmoner bypass yardımı ile koroner bypass operasyonu yapıldı. Aynı seansta 8 mm politetrafloroetilen ringli greft kullanılarak asendan aort ile sağ ana femoral arter arasında ekstra-anatomik bypass operasyonu yapıldı. Hasta sorunsuz iyileşme dönemi ardından taburcu edildi.

Peripheral vascular operations carry high risks for myocardial infarction. In cases with severe coronary artery disease and peripheric vascular disease, combined interventions might have positive effects on patient s recovery without increasing mortality or morbidity. A 67 years old male patient came to our outpatient clinic with rest pain complaint in the right extremity. The examinations showed that his right common iliac artery was occluded and there was severe stenosis on the left anterior descending artery and the right posterior descending coronary artery. We performed a coronary artery bypass surgery with cardiopulmonary bypass. In addition, we simultaneously performed an extra- anatomic ascending aorta-right common femoral artery bypass with a 8 mm knitted polytetrafluoroethylene graft. At length, the patient was discharged without any problems following the recovery period.
Eş Zamanlı Koroner Arter Bypass Ve Asendan Aorta Sağ Femoral Arter Bypass Operasyonu Olgu Sunumu
Keywords: Genel ve Dahili Tıp